Lay Representations of Chronic Diseases in Ghana: Implications for Primary Prevention - de Graft Aikins, A (Ghana Medical Association, 2012)
BACKGROUND: Ghana's health system is ill-equipped to tackle the country's double burden of infectious and chronic diseases. The current focus is on empowering lay communities to adopt healthy practices to prevent chronic diseases. Understanding how individuals make sense of health, illness and chronic illnesses is an important first step to developing practical interventions. METHODS: Six focus group discussions with lay people (N= 51) in Accra, Nkoranza and Kintampo to explore: (1) knowledge of prevalent chronic diseases in Ghana; (2) chronic disease causal theories; and (3) chronic disease treatment. RESULTS: Nineteen conditions were listed cumulatively. Diabetes and hypertension were listed by all groups. Rural groups included HIV/AIDS on their list as well as diseases with alleged spiritual roots, in particular epilepsy and sickle cell disease. Multiple causal theories were presented for diabetes and hypertension; cancers were attributed to toxic foods; asthma attributed to environmental pollution. Biomedical care was preferred by the majority. Lay representations were drawn from multiple sources: medical professionals and chronically ill individuals were the most legitimate knowledge sources. CONCLUSION: This study provides insights on how lay representations of common chronic diseases and their major risk factors provide public health specialists with the conceptual tools to develop primary prevention strategies. The first challenge will be to train health experts to provide accurate information in practical language that lay people can understand and apply to their daily lives. A second challenge will be to develop sustainable behaviour-change interventions. Best practices from other African countries can inform interventions in Ghana.